An Analysis of Affixes in Recount Text of English Text Book Use in Eight Grade of Junior High School - Evawati Nainggola; Lola Chandra Evanty Panggabean; Popy Sinaga; Kartina Rahmadhani Rambe (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
This research is a study of affixation in recount text stories in eight grade English books at SMP Sw Cendramata Medan. The purpose of this study was to determine the types of affixes contained in the story and where the affixes contained in a story in the form of recount text. This affixis can also be found in morphology where morphology is the study of word structure and studying changes in word changes that have their respective groups and have meaning changes in the word.Morphology has 2 types, namely from facies and fection, from facies.  This is related to affixes, to recognize these affixes through 2 ways, namely prefix and suffix. The affix that is located at the beginning of the word is called the prefix while the affix that is located at the end of the word is called the suffix. Based on its location, the affix has 3 types, namely prefix, insertion, and suffix, and based on its function, the affix consists of affixes from facies and inflections.Affixes that cause a change in meaning,recall is often used in a story. This research analyzes and its object is the recount text story contained in the eighth grade reading book. With the title of the story The story of holiday at home. qualitative descriptive is the method used in this research.After the research was conducted, the results of the data analysis found that the use of a suffix was more significant in the recout text story .The result of this research is to find any  the suffix affix that dominates the story and the result of the data is that there are 7 suffixes, namely 7 -s,-ed, -ing, -es, -ers, -ty and –ness.